Hierarchical Culture in Islamic Boarding Schools Related to the Normalization of Bullying Behavior - Restu M. Risqi, Ega; Samsurrohman, Samsurrohman (Riviera Publishing, 2025)
The hierarchical culture in Islamic boarding schools (pondok pesantren) is often seen as an integral part of the education system and the character-building process for students (santri). However, in some cases, this system can contribute to the normalization of bullying, which is perceived as a form of discipline or a mental endurance test. This study aims to analyze how hierarchical structures in pesantren can lead to bullying and how such behavior becomes normalized in students' daily lives. This research employs a qualitative approach, using case studies based on observed incidents. Findings indicate that while hierarchy helps instill values of obedience and discipline, it can also create opportunities for bullying, which is often regarded as a tradition that junior students must endure. Case studies from several Islamic boarding schools in Indonesia, such as Pondok Pesantren Annur 2 Bululawang in Malang and Pondok Pesantren Husnul Khotimah in Kuningan, reveal that bullying persists in various forms. Therefore, it is essential to evaluate the hierarchical system to ensure that positive values are upheld without compromising students' psychological well-being. Additionally, effective preventive measures should be implemented to create a safe and supportive learning environment for all students.